Rancang Bangun Layanan Jaringan Dokumentasi dan Informasi Hukum Menggunakan Framework Laravel Berbasis Web - Mirlani, Muhammad; Gunawan, Gunawan; La Surimi (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2025)
The Legal Documentation and Information Network (JDIH) serves a pivotal role in facilitating access to various legal products. This study aims to design and develop a web-based JDIH service using the Laravel framework, implemented at the Faculty of Mathematics and Natural Sciences, Halu Oleo University. Laravel was selected for its efficiency, ease of management, and support for a Model-View-Controller (MVC) architecture suitable for structured legal information systems. The development process follows the Waterfall methodology, encompassing stages of requirements analysis, system design, implementation, and testing. The research resulted in a JDIH web application designed to facilitate legal information retrieval. The application includes features such as account management, regulatory documentation, abstracts, categories, tags, publication years, and document search and download functionality, accessible to the public. The system is administered by two user types: full-access administrators and sub-administrators with restricted management rights for legal content. Black-box testing confirms that all application features and functionalities perform according to specified requirements. This application is expected to enhance the management and retrieval of legal information within the Faculty of Mathematics and Natural Sciences, contributing to more efficient access and dissemination of legal resources